Educación financiera y su relación con la capacidad de ahorro en el asentamiento humano 8 de mayo, Contamana 2024 - Isuiza Amasifuen, Cornelia (2025)
This research study aimed to determine the relationship between financial education and savings capacity in the Human Settlement 8 de Mayo, Contamana 2024. The research was carried out under an applied approach, with a non-experimental design of descriptive-correlational level. The study population consisted of 1,285 inhabitants, who provided valuable information through the application of surveys. The results show that financial education is rated as regular with 30%, this is due to the indecision shown by the respondents in several aspects: long-term goals, knowledge of savings accounts and credit operations. On the other hand, the savings capacity was rated as regular, obtaining 31%. This result is due to the fact that the respondents indicated that they sometimes plan their personal expenses. In short, a coefficient of 0.875 was demonstrated, indicating a positive and very strong relationship between financial education and savings capacity, with statistical significance less than 0.001 demonstrating the significance of the relationship.